2016
DOI: 10.1093/femsec/fiw059
|View full text |Cite
|
Sign up to set email alerts
|

Rumen bacterial communities shift across a lactation in Holstein, Jersey and Holstein × Jersey dairy cows and correlate to rumen function, bacterial fatty acid composition and production parameters

Abstract: Rumen bacteria form a dynamic, complex, symbiotic relationship with their host, degrading forages to provide volatile fatty acids (VFA) and other substrates as energy to the animal. The objectives were to characterize rumen bacteria in three genetic lines of primiparous dairy cattle, Holstein (HO, n = 7), Jersey (JE, n = 8), and HO × JE crossbreeds (CB, n = 7) across a lactation [3, 93, 183 and 273 days in milk (DIM)] and correlate these factors with VFA, bacterial cell membrane fatty acids (FA), and animal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
50
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 60 publications
11
50
3
Order By: Relevance
“…A decreased abundance of Bacteroidetes in comparison to Firmicutes was resulted in increased milk-fat percentages. Similar results were found by Bainbridge et al (2016), where moderate correlations were found between milk yield, protein percentage, fat yield and bacterial communities. This alone indicates the role of the rumen microbiome in shaping host physiological parameters.…”
Section: Rumen Bacteriasupporting
confidence: 86%
“…A decreased abundance of Bacteroidetes in comparison to Firmicutes was resulted in increased milk-fat percentages. Similar results were found by Bainbridge et al (2016), where moderate correlations were found between milk yield, protein percentage, fat yield and bacterial communities. This alone indicates the role of the rumen microbiome in shaping host physiological parameters.…”
Section: Rumen Bacteriasupporting
confidence: 86%
“…), and Acetobacter (Bainbridge et al . ). As a whole, these correlation studies have not yet added clear conclusions to the generally accepted knowledge regarding bacteria involved in rumen BH or interacting with BH.…”
Section: Rumen Bh: a Microbiota Response To Dietary Ufasmentioning
confidence: 97%
“…With the development and use of new technologies, such as high‐throughput sequencing, our understanding of microbial diversity and complexity has expanded (Jiao et al, ). Recent studies have confirmed that the ruminal microbiota has a significant dynamic response to DMI and rumen fermentation and are related to changes in production parameters such as milk yield and milk composition (Bainbridge, Cersosimo, Wright, & Kraft, ; Derakhshani et al, ). Most research focuses on the relationship between the milk performance and rumen microbiota of dairy cows.…”
Section: Introductionmentioning
confidence: 95%